Export Promotion Agencies : Do They Work? - Lederman, Daniel; Olarreaga, Marcelo; Payton, Lucy (2012)
The number of national export promotion agencies (EPAs) has tripled over the last two decades. While more countries made them part of their export strategy, studies criticized their efficacy in developing countries. EPAs were retooled, partly in response to these critiques. This paper studies the impact of today's EPAs and their strategies, based on new survey data covering 103 developing and developed countries. Results suggest that on average they have a statistically significant effect on exports. Our identification strategies highlight the importance of EPA services for overcoming foreign trade barriers and solving asymmetric information problems associated with exports of heterogeneous goods. There are also strong diminishing returns, suggesting that as far as EPAs are concerned, small is beautiful.